2025 Triumphs and Setbacks: Endovascular Neurosurgery Perspective - Hoz, Samer; Shahrabani, Ahmed (AL-Kindy College Medical Journal, 2026)
In 2025, the field of stroke and carotid artery disease experienced a new update, with the publication of two landmark randomized trials that represent contrasting examples of setback and triumph within endovascular neurosurgery. The MeVO trials proved no superiority of mechanical thrombectomy over best medical therapy for acute ischemic stroke caused by distal- and medium-vessel occlusions. The CREST-2 trials demonstrated a significant reduction in stroke when carotid artery stenting is added to medical therapy. These trials illustrate how recent evidence has simultaneously challenged and reaffirmed the role of neurointerventional therapy.